Improving Elementary Students' Reading Skills Through the Cooperative Integrated Reading and Composition Method - Paskalia Wae; Herwin (Jurnal Ilmiah Sekolah Dasar, 2024)
Reading skills are crucial for everyone, especially for elementary school students. Currently, reading difficulties are commonly encountered, with many students struggling with reading comprehension due to suboptimal reading skills. This study aims to examine the impact of the Cooperative Integrated Reading and Composition (CIRC) learning model on students' reading skills. The research method used is quantitative with a quasi-experimental design. The design applied is a Non-Equivalent Control Group Design with pre-test and post-test. Participants in this study were fifth-grade elementary school students, with a sample of 37 students selected using purposive sampling. These students were divided into two groups: the experimental group consisting of 20 students and the control group consisting of 17 students. Data collection was carried out using assessment rubrics, pre-test and post-test, and structured questionnaires distributed to students to measure reading skills using the CIRC learning model. Data were analyzed using inferential statistics. The results showed a significant difference between the experimental and control groups. The significance value (2-tailed) of 0.000 < 0.05 indicates that the Cooperative Integrated Reading and Composition (CIRC) learning model has a positive impact on the reading skills of fifth-grade students. Based on these results, it can be concluded that the CIRC learning model is effective in improving students' reading skills.